Social Networking Websites impact on Society: Exploring the Influence of Social Networking Websites on Society (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Social networking is a tool used by people all over the world to promote communication. In modern times, people are interacting in many different ways, some by telephone, some by E-mail and some by chatting networks. Every day, people are using the computer to talk with one another and social networking sites are a big reason for this In this paper we will discuss the impact of social networking sites on the real world. Social networking is a dedicated website or other application which enables users to communicate with each other by posting information, comments, messages, images, etc. A social network is a theoretical construct useful in the social sciences to study relationships between individuals, groups, organizations, or even entire societies. A social networking website consists of information about each user .i.e. profile his/her social links, and a variety of additional services. Most social network services are web-based and provide means for users to interact over the Internet, such as e-mail and instant messaging. Social networking sites allow users to share ideas, activities, events, and interests within their individual networks.